Clinical impact of the right ventricular impairment in patients following transcatheter aortic valve replacement - Satoshi Higuchi; Yasuhide Mochizuki; Tadashi Omoto; Hidenari Matsumoto; Tomoaki Masuda; Kazuto Maruta; Atsushi Aoki; Toshiro Shinke (Scientific Reports, 2024)
Abstract The right ventricular (RV) impairment can predict clinical adverse events in patients following transcatheter aortic valve replacement (TAVR) for severe aortic stenosis (AS). Limited reports have compared impact of the left ventricular (LV) and RV disorders. This retrospective study evaluated two-year major adverse cardiac and cerebrovascular events (MACCE) in patients following TAVR for severe AS. RV sphericity index was calculated as the ratio between RV mid-ventricular and longitudinal diameters during the end-diastolic phase. Of 239 patients, 2-year MACCE were observed in 34 (14%). LV ejection fraction was 58 ± 11%. Tricuspid annular plane systolic excursion (TAPSE) and RV sphericity index were 20 ± 3 mm and 0.36 (0.31–0.39). Although the univariate Cox regression analysis demonstrated that both LV and RV parameters predicted the outcomes, LV parameters no longer predicted them after adjustment. Lower TAPSE (adjusted hazard ratio per 1 mm, 0.84; 95% confidence interval, 0.75–0.93) and higher RV sphericity index (adjusted hazard ratio per 0.1, 1.94; 95% confidence interval, 1.17–3.22) were adverse clinical predictors. In conclusion, the RV structural and functional disorders predict two-year MACCE, whereas the LV parameters do not. Impact of LV impairment can be attenuated after development of RV disorders.